2012
DOI: 10.1016/j.jhazmat.2012.02.062
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of unintentional POP emissions from thermal wire reclamation at industrial scrap metal recycling parks in China

Abstract: a b s t r a c tThermal wire reclamation is considered to be a potential source of unintentional persistent organic pollutants (unintentional POPs). In this study, unintentional POP concentrations, including PCDD/Fs, dioxin like PCBs (dl-PCBs), polychlorinated naphthalenes (PCNs), hexachlorobenzene (HxCBz) and pentachlorobenzene (PeCBz), were quantified in flue gas and residual ash emissions from thermal wire reclamation at scrap metal dismantling parks in Zhejiang Province, China. The total average TEQ emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…We have previously reported on several studies of dioxin concentrations, profiles, and emission factors in fly ash samples from coking processes (Liu et al, 2013), primary magnesium smelting (Nie et al, 2011), primary copper smelting processes (Nie et al, 2012a) and secondary copper, aluminum, zinc and lead smelting processes (Ba et al, 2009a,b;Nie et al, 2012b), and iron and steel making (Ba et al, 2009a,b;Lv et al, 2011a,b). In those studies, fly ash samples produced during different incineration or metal smelting stages were collected from the dust arrestors (bag fabric filters, electrostatic precipitator, and cyclones).…”
Section: Information On the Fly Ash Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported on several studies of dioxin concentrations, profiles, and emission factors in fly ash samples from coking processes (Liu et al, 2013), primary magnesium smelting (Nie et al, 2011), primary copper smelting processes (Nie et al, 2012a) and secondary copper, aluminum, zinc and lead smelting processes (Ba et al, 2009a,b;Nie et al, 2012b), and iron and steel making (Ba et al, 2009a,b;Lv et al, 2011a,b). In those studies, fly ash samples produced during different incineration or metal smelting stages were collected from the dust arrestors (bag fabric filters, electrostatic precipitator, and cyclones).…”
Section: Information On the Fly Ash Samplesmentioning
confidence: 99%
“…Previous studies have reported on PCDD/F concentrations and profiles of fly ash samples from coking processes (Liu et al, 2013), primary magnesium smelting processes (Nie et al, 2011), primary copper smelting processes, (Nie et al, 2012a) and secondary copper, aluminum, zinc, and lead smelting processes (Ba et al, 2009a,b;Nie et al, 2012b), and iron and steel making (Lv et al, 2011a,b). In this study, data from studies on the PCDD/F levels and profiles of fly ash were summarized and compared (Ba et al, 2009a,b;Nie et al, 2011Nie et al, , 2012aLv et al, 2011aLv et al, ,b, 2013; and PCDD/F data from 113 fly ash samples from 14 types of industrial thermal sources were systematically evaluated and compared.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few studies have focused on the emissions of PCBs in other sources, including iron ore sintering plant (Tian et al, 2012), metallurgical process (Nie et al, 2011(Nie et al, , 2012, and medical waste incineration (Chen et al, 2015) in China. Unfortunately, studies on PCB emissions from MWIs in China are extremely limited (Yan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to these POPs is a matter of great concern because of their toxicity, which is known to induce hormonedependent cancers and undesirable reproductive effects in humans and wildlife. POPs are difficult to degrade and can be easily accumulated and magnified in organisms, making POPs considerably harmful to humans and the environment (Nie et al, 2012). PCDD/Fs and PCBs are released as impurities during several chemical production processes, such as polychlorophenols, polychlorobenzenes, and organic chlorinated pesticides, which also represent the important sources of PCDD/Fs and PCBs in China (Ni et al, 2005;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%